2015
DOI: 10.1016/j.actamat.2015.06.048
|View full text |Cite
|
Sign up to set email alerts
|

A combined calorimetric and computational study of the energetics of rare earth substituted UO2 systems

Abstract: The energetics of rare earth substituted UO 2 solid solutions (U 1-x Ln x O 2-0.5x+y , where Ln = La, Y, and Nd) are investigated employing a combination of calorimetric measurements and density functional theory based computations. Calculated and measured formation enthalpies agree within 10 kJ/mol for stoichiometric oxygen/metal compositions. To better understand the factors governing the stability and defect binding in rare earth substituted urania solid solutions, systematic trends in the energetics are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…Charge balance can also occur by host cation oxidation (U 4+ −U 5+ −U 6+ ). 141,142 Higher valence doping is not common although there are studies on doping of urania with Nb 2 O 5 to improve creep behavior. 143 In this case, it is likely that extra oxygen atoms go into interstitial positions or the system can be stabilized by localizing electrons on cation sites.…”
Section: Fluorite Structure Defects and Derivativesmentioning
confidence: 99%
See 3 more Smart Citations
“…Charge balance can also occur by host cation oxidation (U 4+ −U 5+ −U 6+ ). 141,142 Higher valence doping is not common although there are studies on doping of urania with Nb 2 O 5 to improve creep behavior. 143 In this case, it is likely that extra oxygen atoms go into interstitial positions or the system can be stabilized by localizing electrons on cation sites.…”
Section: Fluorite Structure Defects and Derivativesmentioning
confidence: 99%
“…Mazeina et al 226 have shown for the UO 2 −CaO and UO 2 −YO 1.5 systems that partial oxidation of U to form phases in the UO 2 −UO 3 −CaO and UO 2 −UO 3 −YO 1.5 ternary systems significantly stabilizes the solid solutions, as demonstrated by the negative enthalpies of formation. Experiments by Zhang et al 56,141 later demonstrated that the uranium oxidation state can also be 5+ as an intermediate between UO 2 and UO 3 4.2.3. Multicomponent Systems.…”
Section: Thermodynamic Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, H tends to form [O 2– H + ] − in PuO 2 by binding with lattice O whereas interstitial H + is involved in UO 2 . This difference results from the dual nature of 5f electrons: Pu 5f electrons in PuO 2 are more localized and less favorable to participate in further chemical bonding or vice versa for UO 2 . , In contrast, the substitutional metal site in fluorite-type oxides such as UO 2 , ThO 2 , and CeO 2 is determined to be the exclusive site for low-concentration transition-metal (TM) impurities. , This conclusion is proposed to hold for PuO 2 despite the fact that a comprehensive study on TM behaviors in PuO 2 is lacking; the only exception is the DFT energetics and structures of Fe in PuO 2 , which partially supports the conclusion …”
Section: Introductionmentioning
confidence: 99%